Evaluation of the Effects of Various Sound Pressure Levels on the Level of Serum Aldosterone Concentration in Rats - Nassiri, Parvin (Noise Health, 2017)
INTRODUCTION: Noise exposure may have anatomical, nonauditory, and auditory influences. Considering nonauditory impacts, noise exposure can cause alterations in the automatic nervous system, including increased pulse rates, heightened blood pressure, and abnormal secretion of hormones. The present study aimed at examining the effect of various sound pressure levels (SPLs) on the serum aldosterone level among rats. MATERIALS AND METHODS: A total of 45 adult male rats with an age range of 3 to 4 months and a weight of 200 ± 50 g were randomly divided into 15 groups of three. Three groups were considered as the control groups and the rest (i.e., 12 groups) as the case groups. Rats of the case groups were exposed to SPLs of 85, 95, and 105 dBA. White noise was used as the noise to which the rats were exposed. To measure the level of rats’ serum aldosterone, 3 mL of each rat’s sample blood was directly taken from the heart of anesthetized animals by using syringes. The taken blood samples were put in labeled test tubes that contained anticoagulant Ethylenediaminetetraacetic acid. In the laboratory, the level of aldosterone was assessed through Enzyme-linked immunosorbent assay protocol. The collected data were analyzed by the use of Statistical Package for Social Sciences (SPSS) version 18. RESULTS: The results revealed that there was no significant change in the level of rats’ serum aldosterone as a result of exposure to SPLs of 65, 85, and 95 dBA. However, the level of serum aldosterone experienced a remarkable increase after exposure to the SPL of 105 dBA (P < 0.001). Thus, the SPL had a significant impact on the serum aldosterone level (P < 0.001). In contrast, the exposure time and the level of potassium in the used water did not have any measurable influence on the level of serum aldosterone (P = 0.25 and 0.39). CONCLUSION: The findings of this study demonstrated that serum aldosterone can be used as a biomarker in the face of sound exposure.